HNTs-rGO nano composite material as well as preparation method and application thereof

By using Elosite nanotube-reduced graphene oxide (HNTs-rGO) nanocomposites to modify the electrode, the problems of complexity, high cost and low sensitivity of detection of nitricamide in the prior art were solved, and the electrochemical detection effect of fast, sensitive and selective was achieved.

CN119706815APending Publication Date: 2025-03-28SHANXI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411893211.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art has problems such as complex and cumbersome detection of nitricamide, high cost, low sensitivity, long recognition time and insignificant recognition effect.

Method used

The composite material was prepared by sonication, activation treatment and heating reaction, and electrochemical detection of nitricamide.

Benefits of technology

The rapid, sensitive and selective electrochemical detection of nitricamide is achieved, reducing the detection cost and complexity, and improving the detection sensitivity and identification efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706815A_ABST
    Figure CN119706815A_ABST
Patent Text Reader

Abstract

The invention discloses an HNTs-rGO nano composite material as well as a preparation method and application thereof, and belongs to the technical field of electrochemical detection of nano composite materials. The HNTs-rGO nano composite material is prepared by modifying halloysite nanotubes (HNTs) to the surface of reduced graphene oxide (rGO), and the composite material not only combines the advantages of large specific surface area, high electron transfer rate and the like of the rGO, but also has the adsorption recognition capability of the HNTs to niclosamide; therefore, the composite material is further modified on the surface of a glassy carbon electrode (GCE) to prepare a novel electrochemical sensing platform, and electrochemical sensing of niclosamide (NA) is realized. The invention provides a simple and rapid method for detecting niclosamide based on the excellent electrochemical performance of HNTs-rGO.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical detection of nanocomposite materials, and specifically relates to a HNTs-rGO nanocomposite material and a preparation method and application thereof. Background Art

[0002] Niclosamide (NA) is a commonly used eel killer and molluscicide in agriculture. It is also a human antiparasitic drug. It was approved by the US Food and Drug Administration in 1982 and included in the World Health Organization's Essential Medicines List. However, the widespread use of niclosamide has also brought certain problems. For example, it has high toxicity to some aquatic organisms, such as fish, aquatic snails, and snails. Long-term intake will cause irreversible harm to human health. Current detection methods for niclosamide include biological methods, titration methods, UV-visible spectrophotometry, chromatography, fluorescence methods, electrochemical analysis methods, etc. Among them, electrochemical analysis methods have the advantages of high sensitivity, good selectivity, rapid response time, and low cost, and can directly detect the target in different samples. Therefore, electrochemical detection of niclosamide is of great significance.

[0003] Halloysite (HNTs) is a kaolinite mineral with a natural nanotube structure. The siloxane groups on its outer surface are reactive with the aluminum alcohol groups (Al-OH) on its inner surface. Its surface properties can be modified to change them. It has a wide range of applications in electrochemical sensing, drug delivery, catalysis, etc. Modified HNTs are high-quality carriers of nanomaterials and can improve the dispersion of materials in the system.

[0004] Carbon-based materials such as carbon nanotubes, fullerenes, and graphene have a wide range of applications in the field of materials due to their high specific surface area, uniform surface morphology, and developed pore structure. Among them, reduced graphene oxide has excellent properties such as high electrical conductivity, large specific surface area, high mechanical strength, and good chemical stability. Therefore, halloysite nanotubes are modified on the surface of reduced graphene oxide. This composite material combines the adsorption and recognition effects of halloysite nanotubes with the excellent electrochemical properties of reduced graphene oxide, which can improve the specific recognition and selectivity of the electrode.

[0005] In view of this, it is of great significance to develop composite materials of reduced graphene oxide modified by halloysite nanotubes to achieve simple, rapid and sensitive electrochemical detection of niclosamide. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a halloysite nanotube-reduced graphene oxide (HNTs-rGO) composite material and electrochemically detecting niclosamide (NA). The (HNTs-rGO) composite material of the present invention can realize simple, rapid and sensitive electrochemical detection of niclosamide, and can solve the technical problems of the prior art such as complexity, high cost, low sensitivity, long recognition time and unclear recognition effect.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A method for preparing a HNTs-rGO nanocomposite material comprises the following steps:

[0009] Step 1: Preparation of reduced graphene oxide rGO:

[0010] The graphene oxide GO is dissolved in ultrapure water, and then ultrasonically treated. Then, ammonia water and hydrazine hydrate are added, and the mixture is heated for reaction after ultrasonic homogenization. After the reaction is completed, the mixture is washed, filtered, and freeze-dried to obtain reduced graphene oxide rGO.

[0011] Step 2: Preparation of Halloysite Nanotubes-Reduced Graphene Oxide HNTs-rGO:

[0012] The reduced graphene oxide rGO prepared in step 1 is dissolved in ultrapure water and uniformly dispersed by ultrasonication. Then, EDCI and NHS are added to activate the carboxylic acid groups in the reduced graphene oxide rGO. Then, halloysite HNTs are added and heated to react under stirring. After the reaction is completed, the HNTs-rGO nanocomposite material is obtained by washing, suction filtration and freeze drying.

[0013] Furthermore, in the step 1, the amount of graphene oxide GO is 20-50 mg, the amount of ultrapure water is 20-60 mL, the amount of ammonia water is 600-1500 μL, and the amount of hydrazine hydrate is 65-160 μL.

[0014] Furthermore, the conditions for the heating reaction in step 1 are: oil bath heating, temperature 95-100° C., time 4-6 h.

[0015] Furthermore, in the step 2, the amount of reduced graphene oxide rGO is 10-30 mg, the amount of ultrapure water is 20-60 mL, the amount of EDCI is 20-40 mg, the amount of NHS is 15-35 mg, and the amount of HNTs is 10-30 mg.

[0016] Furthermore, the activation treatment time in step 2 is 0.5-1h.

[0017] Furthermore, the conditions for the heating reaction in step 2 are: oil bath heating, temperature 55-60° C., time 12-14 h.

[0018] A HNTs-rGO nanocomposite material is prepared by the preparation method as described above.

[0019] The application of HNTs-rGO nanocomposites as described above was used for electrochemical detection of niclosamide.

[0020] A modified electrode comprises a glassy carbon electrode modified with the HNTs-rGO nanocomposite material as described above.

[0021] The modified electrode as described above was used for electrochemical detection of niclosamide.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The HNTs-rGO nanocomposite prepared by the present invention has both the adsorption and recognition effect of halloysite nanotubes and the excellent electrochemical performance of reduced graphene oxide. The synergistic effect of the two further amplifies the electrochemical signal and improves the specific recognition and selectivity of the electrode, which can achieve rapid and sensitive detection of niclosamide. This new electrochemical sensor for niclosamide detection has the characteristics of rapidity, high sensitivity, good selectivity, simplicity and ease of use, and is superior to other detection methods.

[0024] (2) The present invention studied the electrochemical behavior of niclosamide on the surface of an electrode modified with an HNTs-rGO nanocomposite material by DPV, and found that a lower detection limit was obtained within a wider linear range, which greatly improved the specific recognition effect of the modified electrode on niclosamide and the detection sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 SEM image of GO (A); SEM image of HNTs-rGO (B); EDS energy spectrum of HNTs-rGO (C).

[0026] Figure 2 Infrared spectra of GO, rGO, HNTs and HNTs-rGO (A); Raman spectra of rGO and HNTs-rGO (B).

[0027] Figure 3 XPS spectra of rGO, HNTs-rGO (A), C1s of rGO (B), C1s of HNTs-rGO (C), Si2p (D) and Al2p (E) XPS spectra.

[0028] Figure 4For bare GCE, rGO / GCE and HNTs-rGO / GCE in 5 mM [Fe(CN)6] 3- / 4- Cyclic voltammogram in solution (A) and cyclic voltammogram in 10 μM niclosamide solution (B).

[0029] Figure 5 Cyclic voltammograms of HNTs-rGO / GCE to 10 μM niclosamide at different scan rates (A); The linear relationship between the peak current of niclosamide and the square root of the scan rate (B).

[0030] Figure 6 DPV response diagram of HNTs-rGO / GCE to 10 μM NA under different pH conditions (A); corresponding current response intensity (B).

[0031] Figure 7 Effects of modification amount (A) and enrichment time (B) on the electrochemical signal of HNTs-rGO / GCE in detecting niclosamide.

[0032] Figure 8 The DPV graph (A) and linear graph (B) of different concentrations of niclosamide detected in 0.1 M PBS (pH=8.0) are shown.

[0033] Fig. 9 To determine the anti-interference of HNTs-rGO / GCE for niclosamide detection. DETAILED DESCRIPTION

[0034] In order to facilitate understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0035] Preparation Example 1

[0036] A method for preparing a HNTs-rGO nanocomposite material comprises the following steps:

[0037] (1) Preparation of reduced graphene oxide (rGO):

[0038] 40 mg of GO was ultrasonically treated in 40 mL of ultrapure water for 5 h to obtain a uniform dispersion, and then 1200 μL of ammonia and 128 μL of hydrazine hydrate were added in sequence and ultrasonicated for 20 min. After the ultrasonication was uniform, the suspension was placed in an oil bath and heated to 95 ° C for 4 h. After cooling to room temperature, the product was washed with deionized water several times, filtered and freeze-dried to obtain rGO black powder.

[0039] (2) Preparation of Halloysite Nanotubes-Reduced Graphene Oxide (HNTs-rGO):

[0040] Take 20 mg of the prepared reduced graphene oxide (rGO) and disperse it evenly in 40 mL of ultrapure water by ultrasonication, add 25 mg of EDCI and 18 mg of NHS to activate the carboxylic acid groups in GO for 0.5 h, then add 30 mg of HNTs, heat the oil bath to 60 ° C, and stir magnetically for 12 h. After the reaction is completed, the product is washed with deionized water several times, vacuum filtered, and freeze-dried to obtain HNTs-rGO nanocomposites.

[0041] Preparation Example 2

[0042] A method for preparing a HNTs-rGO nanocomposite material comprises the following steps:

[0043] (1) Preparation of reduced graphene oxide (rGO):

[0044] 45 mg of GO was ultrasonically treated in 50 mL of ultrapure water for 4 h to obtain a uniform dispersion, and then 1300 μL of ammonia and 140 μL of hydrazine hydrate were added in sequence and ultrasonicated for 20 min. After the ultrasonication was uniform, the suspension was placed in an oil bath and heated to 100 ° C for 4 h. After cooling to room temperature, the product was washed with deionized water several times, filtered and freeze-dried to obtain rGO black powder.

[0045] (2) Preparation of Halloysite Nanotubes-Reduced Graphene Oxide (HNTs-rGO):

[0046] Take 30 mg of the prepared reduced graphene oxide (rGO) and disperse it evenly in 50 mL of ultrapure water by ultrasonication, add 30 mg of EDCI and 25 mg of NHS to activate the carboxylic acid groups in GO for 0.5 h, then add 30 mg of HNTs, heat the oil bath to 50 ° C, and stir magnetically for 12 h. After the reaction is completed, the product is washed with deionized water several times, vacuum filtered, and freeze-dried to obtain HNTs-rGO nanocomposites.

[0047] Application Example 1

[0048] The HNTs-rGO nanocomposite material prepared in Example 1 was used for electrochemical detection of niclosamide, and the detection method was as follows:

[0049] (1) Preparation of HNTs-rGO modified electrodes:

[0050] First, the surface of the glassy carbon electrode (GCE) was polished, and then the GCE was cleaned with ethanol and deionized water under ultrasonic conditions. After the electrode was cleaned, the HNTs-rGO powder prepared in Example 1 was added to a mixture of ethanol, water and Nafion, and ultrasonically treated to prepare a 2 mg / mL dispersion; then 4 μL of the HNTs-rGO dispersion was dropwise applied to the surface of the GCE and dried under an infrared lamp to obtain a modified electrode HNTs-rGO / GCE;

[0051] (2) Electrochemical characterization of HNTs-rGO modified electrode:

[0052] The HNTs-rGO / GCE modified electrode was immersed in a mixed solution containing 0.1M KCl, 5mM K3[Fe(CN)6], and 5mM K4[Fe(CN)6], and a cyclic voltammetry (CV) test was performed. HNTs-rGO / GCE showed a higher peak current value.

[0053] (3) Electrochemical detection of niclosamide (NA):

[0054] HNTs-rGO / GCE was immersed in a PBS buffer solution with pH = 8.0 containing 10 μM niclosamide, and a differential pulse voltammetry (DPV) test was carried out. By measuring the current response signal of DPV, it was determined whether there was a response to niclosamide and the effect of the response. The experiment found that HNTs-rGO / GCE can successfully perform electrochemical detection of niclosamide and show high selectivity.

[0055] Application Example 2

[0056] The HNTs-rGO nanocomposite prepared in Example 2 was used for electrochemical detection of niclosamide, and the detection method was as follows:

[0057] (1) Preparation of HNTs-rGO modified electrodes:

[0058] First, the surface of the glassy carbon electrode (GCE) was polished, and then the GCE was cleaned with ethanol and deionized water under ultrasonic conditions. After the electrode was cleaned, the HNTs-rGO powder prepared in Example 2 was added to a mixture of ethanol, water and Nafion, and ultrasonically treated to prepare a 2 mg / mL dispersion; then 6 μL of the HNTs-rGO dispersion was drop-coated on the surface of the GCE and dried under an infrared lamp to obtain a modified electrode HNTs-rGO / GCE;

[0059] (2) Electrochemical characterization of HNTs-rGO modified electrode:

[0060] The HNTs-rGO / GCE modified electrode was immersed in a mixed solution containing 0.1M KCl, 5mM K3[Fe(CN)6], and 5mM K4[Fe(CN)6], and a cyclic voltammetry (CV) test was performed. HNTs-rGO / GCE showed a higher peak current value.

[0061] (3) Electrochemical detection of niclosamide (NA):

[0062] HNTs-rGO / GCE was immersed in a PBS buffer solution with pH = 8.0 containing 10 μM niclosamide, and a differential pulse voltammetry (DPV) test was carried out. By measuring the current response signal of DPV, it was determined whether there was a response to niclosamide and the effect of the response. The experiment found that HNTs-rGO / GCE can successfully perform electrochemical detection of niclosamide and show high selectivity.

[0063] The HNTs-rGO nanocomposite material prepared in Preparation Example 1 was used for characterization and analysis below:

[0064] Figure 1 The SEM image of A shows the surface morphology of GO, where the relatively flat two-dimensional sheet structure of graphene oxide can be clearly observed; Figure 1 B is the SEM image of the HNTs-rGO nanocomposite, where it can be observed that the HNTs-rGO nanocomposite presents a wrinkled morphology, and many HNTs with tubular structures are evenly distributed on the surface of rGO; Figure 1 C is the EDS spectrum of HNTs-rGO. It can be seen from the figure that the main elements contained in the HNTs-rGO nanocomposite material are C, O, Si, and Al, among which Si and Al elements are derived from HNTs, confirming that the halloysite nanotubes are successfully modified on the rGO surface.

[0065] Figure 2 A is the infrared spectra of GO, rGO, HNTs and HNTs-rGO nanocomposites. -1 With 1727cm -1 The peaks at 1550cm-1 correspond to the stretching vibration of C=C and C=O of GO, respectively. -1 The C=C skeleton vibration peak signal appeared at 3617 cm -1 With 3695cm -1 The two characteristic peaks are the stretching vibration peaks of the hydroxyl groups on the outer surface of HNTs, 1026cm -1 , 910cm -1 , 687cm -1 , 537cm -1, 465cm -1 They correspond to the stretching vibration of Si-O bond, the modification of internal hydroxyl OH, the stretching vibration of vertical Si-O, the vibration of Al-O-Si bond and the deformation vibration of Si-O-Si bond. The infrared spectrum of HNTs-rGO nanocomposite is different from that of rGO and HNTs. -1 ,3617cm -1 , 1026cm -1 , 910cm -1 , 687cm -1 , 537cm -1 , 465cm -1 The characteristic peaks of HNTs correspond to each other, and the characteristic peak of graphene is 3416cm -1 、1550cm -1 There are corresponding peaks at all locations, that is, the composite material has the characteristic peaks of both halloysite and rGO, which further proves the successful preparation of HNTs-rGO nanocomposite materials.

[0066] Figure 2 B is the Raman image of rGO and HNTs-rGO. The Raman spectra of the two materials show two obvious characteristic peaks, namely 1351.62 cm -1 D belt at 1591.72cm -1 The G band at the D band is compared with the G band intensity ratio (I D / I G ) characterizes the degree of defects on the graphene surface. Compared with rGO, I D / I G (1.55), I of HNTs-rGO D / I G (1.80) increased, which is attributed to the modification of the hollow tubular structure of halloysite on the surface of reduced graphene oxide, which changed the surface structure of rGO and increased many defect sites on the graphene surface, thus leading to I D / I G increase.

[0067] Figure 3 A is the XPS spectra of rGO and HNTs-rGO. It can be seen from the figure that both rGO and HNTs-rGO contain C, N, and O elements, but Al and Si elements also appear in HNTs-rGO, which is due to the modification of HNTs on the rGO surface; Figure 3 B and 3C are high-resolution spectra of C1s in rGO and HNTs-rGO, respectively, and there are five typical carbon bonds: CC (284.6 eV), CN (285.4 eV), CO (286.2 eV), C=O (287.4 eV) and OC=O (288.4 eV); Figure 3 D and 3E respectively fit the Si2p and Al2p of HNTs-rGO to obtain Si2p 1 / 2 (104.81eV), Si2p 3 / 2 (102.17 eV) and Al2p (75.81 eV), confirming that halloysite was successfully loaded on the rGO surface.

[0068] Figure 4 A is bare GCE, rGO / GCE and HNTs-rGO / GCE in 5 mM [Fe(CN)6] 3- / 4- Cyclic voltammograms in solution show that all three electrodes show a pair of redox peaks in the solution. The peak current of bare GCE is the smallest, rGO / GCE is in the middle, and HNTs-rGO / GCE is the largest. The results show that the excellent conductivity of rGO can promote the efficiency of electron transfer, and the presence of HNTs in the composite material can promote the dispersion of rGO without agglomeration, making it more conductive than rGO. The results show that the constructed HNTs-rGO / GCE sensing platform has excellent electrochemical properties.

[0069] Figure 4 B is the cyclic voltammogram of bare GCE, rGO / GCE and HNTs-rGO / GCE to 10μM niclosamide. It can be observed from the figure that the three electrodes all show a pair of reversible redox peaks and an irreversible reduction peak in the solution, while the corresponding current peak is almost not observed on rGO / GCE, indicating that rGO / GCE has no electrochemical response to niclosamide. The redox peak current of HNTs-rGO / GCE is higher than that of the bare electrode, and the peak potential is further shifted, indicating that HNTs-rGO / GCE can recognize niclosamide and amplify its electrochemical signal, so HNTs-rGO / GCE can be used for effective electrochemical detection of niclosamide.

[0070] Figure 5 The CV response diagram of HNTs-rGO / GCE to niclosamide at different scan rates shows that there are obvious oxidation peaks and reduction peaks in the CV curve of niclosamide, indicating that the reaction of niclosamide on the electrode surface is reversible. At the same time, with the increase of the scan rate, the electrochemical response signal also gradually increases, and the peak current is in the range of 40 to 280 mV / s with v 1 / 2 It shows a good linear correlation, indicating that the electron transfer reaction of niclosamide on HNTs-rGO / GCE is a typical diffusion-controlled process.

[0071] Figure 6To investigate the electrochemical behavior of niclosamide on HNTs-rGO modified electrode under different pH conditions, the electrochemical response signal of HNTs-rGO / GCE to niclosamide was investigated by DPV method in PBS solutions (pH = 5.0-10.0) containing 10 μM niclosamide. Figure 6 A), as the pH gradually increases, the peak potential shifts negatively, and at pH = 8.0, the peak current is the largest ( Figure 6 B). This is because a strong acidic solution with a low pH value is not conducive to the electrochemical redox of hydroxylamine and nitroso groups, while a strong alkaline solution with a high pH value cannot provide the necessary reaction conditions for the redox of NA. Therefore, pH = 8.0 is selected as the optimal value.

[0072] Figure 7 A and 7B show the effects of different enrichment times and modification material volumes on niclosamide detection. It can be seen that 4 μL is the optimal modification amount and 150 s is the best enrichment time.

[0073] Figure 8 The DPV response diagram of HNTs-rGO / GCE to different concentrations of niclosamide under the optimal experimental conditions. Figure 8 A shows that the peak current of niclosamide increases with the increase of concentration, and the i value shows a strong concentration dependence. In the two ranges of 0.2-4 μM and 4-40 μM, the electrochemical signal of NA shows a good linear relationship with its concentration, which can be expressed by the linear equation i(μA)=2.609+4.009logc(μM)(R 2 =0.9916), i(μA)=-2.914+12.90logc(μM)(R 2 =0.9964) means ( Figure 8 B), and the limit of detection (LOD) was 66.67 nM (signal-to-noise ratio S / N=3).

[0074] Fig. 9 To determine the anti-interference of HNTs-rGO / GCE to niclosamide detection, under the optimal conditions, HNTs-rGO / GCE was used to detect 10 μM niclosamide and 100 μM glucose, citric acid, ascorbic acid, Na + 、Ni 2+ , K + , Cu 2+ , Ca 2+ The DPV detection was performed on the 10 μM niclosamide mixed system of cinchonine, dopamine and bile acid, and the results were plotted as a bar graph. It can be seen that after the addition of the interfering substance, the current response generated by niclosamide was not significantly disturbed, indicating that the prepared HNTs-rGO / GCE has good anti-interference ability.

[0075] The above description is only for better explaining the embodiments of the present invention, and is not intended to limit the present invention. Any modification or equivalent substitution that does not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.

Claims

1. A method for preparing a HNTs-rGO nanocomposite material, characterized in that: The following steps are involved: Step 1: Preparation of reduced graphene oxide rGO: The graphene oxide GO is dissolved in ultrapure water, and then ultrasonically treated. Then, ammonia water and hydrazine hydrate are added, and the mixture is heated for reaction after ultrasonic homogenization. After the reaction is completed, the mixture is washed, filtered, and freeze-dried to obtain reduced graphene oxide rGO. Step 2: Preparation of Halloysite Nanotubes-Reduced Graphene Oxide HNTs-rGO: The reduced graphene oxide rGO prepared in step 1 is dissolved in ultrapure water and uniformly dispersed by ultrasonication. Then, EDCI and NHS are added to activate the carboxylic acid groups in the reduced graphene oxide rGO. Then, halloysite HNTs are added and heated to react under stirring. After the reaction is completed, the HNTs-rGO nanocomposite material is obtained by washing, suction filtration and freeze drying.

2. The method for preparing the HNTs-rGO nanocomposite material according to claim 1, characterized in that: In the step 1, the amount of graphene oxide GO is 20-50 mg, the amount of ultrapure water is 20-60 mL, the amount of ammonia water is 600-1500 μL, and the amount of hydrazine hydrate is 65-160 μL.

3. The method for preparing the HNTs-rGO nanocomposite material according to claim 1, characterized in that: The conditions for the heating reaction in step 1 are: oil bath heating, temperature 95-100° C., time 4-6 h.

4. The method for preparing the HNTs-rGO nanocomposite material according to claim 1, characterized in that: In the step 2, the amount of reduced graphene oxide rGO is 10-30 mg, the amount of ultrapure water is 20-60 mL, the amount of EDCI is 20-40 mg, the amount of NHS is 15-35 mg, and the amount of HNTs is 10-30 mg.

5. The method for preparing the HNTs-rGO nanocomposite material according to claim 1, characterized in that: The activation treatment time in step 2 is 0.5-1h.

6. The method for preparing the HNTs-rGO nanocomposite material according to claim 1, characterized in that: The conditions for the heating reaction in step 2 are: heating in an oil bath, a temperature of 55-60° C., and a time of 12-14 h.

7. A HNTs-rGO nanocomposite material, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. The use of the HNTs-rGO nanocomposite material according to claim 7, characterized in that: For electrochemical detection of niclosamide.

9. A modified electrode, characterized in that: It comprises a glassy carbon electrode modified with the HNTs-rGO nanocomposite material according to claim 7.

10. The use of the modified electrode according to claim 9, characterized in that: For electrochemical detection of niclosamide.

Citation Information

Patent Citations

  • Preparation and application of electrochemical sensor based on halloysite nanotube and graphene

    CN109307699A

  • Graphene-endellite composite aerogel material and preparation method thereof

    CN109692152A

  • Graphene oxide loaded halloysite modified styrene-butadiene rubber and preparation method thereof

    CN109762221A

  • Preparation method of phosphorus-doped porous carbon microsphere as niclosamide oxidase sensor

    CN111239215A

  • Preparation method of halloysite nanotube / graphene oxide composite material and application thereof

    CN113244890A